Epidermal growth factor in the treatment of radiogenic proctitis - Nery González; Francisco Hernández-Bernal; Tania González; Josefina Lugo; Juan J Lence; Maria A Pascual; Pedro López-Saura (Biotecnología Aplicada)
Radiogenic proctitis is a frequent complication of therapeutic radiation at the pelvic region. The aim of this study was to determine the efficacy of the epidermal growth factor (EGF) in treating patients with proctitis as a complication of radiotherapy of gynecological tumors. A phase II, placebo-controlled, randomized, double blind clinical trial was carried out. The treatment groups were: A) a solution of human recombinant epidermal growth factor (10 µg/ ml) in carboxymethyl cellulose or B) placebo (carboxymethylcellulose solution alone); the treatment was administered as a retention enema (20 mL) twice a day after bowel movement for 6 months. We included women of 18-75 years of age with proctitis as a complication of an ionizing radiation treatment of gynecological malignant tumors, confirmed by endoscopy, who gave their consent to participate. Thirty-seven patients were included. The basic demographic variables and were homogeneous among groups, which were comparable. There were more responses in group A (EGF) than in the control (placebo), but the difference was not statistically significant. Considering only those patients who completed the treatment, the difference in response was greater with EGF (86% vs 60%). The symptoms disappeared more rapidly in the group treatedwith EGF (p=0.027 and p=0.016, for bleeding and tenesmus, respectively). The product under study was well tolerated. Although there are signs of improvement in some symptoms, the sample was too small to demonstrate the effectiveness of Hebervis in the treatment of proctitis.